2016
DOI: 10.1021/jacs.6b02221
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a C3 Deoxygenation Pathway Reveals a Key Branch Point in Aminoglycoside Biosynthesis

Abstract: Apramycin is a clinically interesting aminoglycoside antibiotic (AGA) containing a highly unique bicyclic octose moiety, and this octose is deoxygenated at the C3 position. Although the biosynthetic pathways for most 2-deoxystreptamine-containing AGAs have been well characterized, the pathway for apramycin biosynthesis, including the C3 deoxygenation process, has long remained unknown. Here we report detailed investigation of apramycin biosynthesis by a series of genetic, biochemical and bioinformatical studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 55 publications
2
69
1
Order By: Relevance
“…In contrast to the previous proposal in which the C3 deoxygenation occurs as the penultimate step, biochemical studies have shown that the C3 deoxygenation is catalyzed by the radical SAM diol dehydratase AprD4 and its NADPH-dependent reductase partner AprD3 20, 39, 40 . This C3 deoxygenation reaction does not occur on oxyapramycin but on the pseudodisaccharide substrate paromamine, demonstrating the two parallel biosynthetic pathways, which affords oxyapramycin and apramycin, respectively ( Figure 3) 20 . Consistent with this observation, biochemical analysis has shown that AprQ, a FAD-dependent dehydrogenase, catalyzes the C6' dehydrogenation of both paromamine and lividamine, with the latter as the preferred substrate 20 .…”
Section: Parallel Pathways In Apramycin Biosynthesiscontrasting
confidence: 64%
See 2 more Smart Citations
“…In contrast to the previous proposal in which the C3 deoxygenation occurs as the penultimate step, biochemical studies have shown that the C3 deoxygenation is catalyzed by the radical SAM diol dehydratase AprD4 and its NADPH-dependent reductase partner AprD3 20, 39, 40 . This C3 deoxygenation reaction does not occur on oxyapramycin but on the pseudodisaccharide substrate paromamine, demonstrating the two parallel biosynthetic pathways, which affords oxyapramycin and apramycin, respectively ( Figure 3) 20 . Consistent with this observation, biochemical analysis has shown that AprQ, a FAD-dependent dehydrogenase, catalyzes the C6' dehydrogenation of both paromamine and lividamine, with the latter as the preferred substrate 20 .…”
Section: Parallel Pathways In Apramycin Biosynthesiscontrasting
confidence: 64%
“…Consistent with this observation, biochemical analysis has shown that AprQ, a FAD-dependent dehydrogenase, catalyzes the C6' dehydrogenation of both paromamine and lividamine, with the latter as the preferred substrate 20 . Remarkably, AprQ is also able to act on the tripseudodisaccharide substrate gentamicin X2 and G418 and, in the latter case, produce a novel gentamicin analogue with a C6' carboxylate 20 . A similar observation was also made on AprD4 and AprD3, which are able to act on tripseudodisaccharide substrates, such as kanamycin C and kanamycin B 40 .…”
Section: Parallel Pathways In Apramycin Biosynthesissupporting
confidence: 52%
See 1 more Smart Citation
“…Streptomyces is the largest genus of Actinobacteria with an extremely high GC content in their genomes. Streptomyces have evolved to produce a wide variety of bioactive secondary metabolites, including antibiotics, anticancer agents, herbicides, and immunosuppressants [ [154] , [155] , [156] , [157] , [158] , [159] , [160] , [161] , [162] , [163] , [164] , [165] , [166] ]. However, the potential for metabolite biosynthesis is not fully explored.…”
Section: Applications Of Crispr-cas9/cas12a Biotechnology In Bacteriamentioning
confidence: 99%
“…These cell culture-based findings were corroborated with observations from a whole-organism model when tissue extracts of homozygous ABHD3 knockout mice were compared with extracts of WT mice, and C14-lysophosphatidylcholine was found to accumulate in addition to three other phosphatidylcholines ( 74 ). Ex-vivo metabolomics profiling also led to the discovery and characterization of sedoheptulose-1,7-bisphosphatase, which is involved in riboneogenesis in yeast ( 75 ), a radical SAM dehydratase as well as an NADPH-dependent reductase involved in the biosynthesis of the aminoglycoside antibiotic apramycin in Streptomyces tenebrarius ( 76 ), and the yeast DLD3 protein as a D-2-hydroxyglutarate-pyruvate transhydrogenase potentially involved in the shuttling of reducing equivalents from cytosolic NADH to the mitochondrial electron transfer chain ( 77 ). Most recently, the human FGGY protein and its yeast ortholog were also identified as D-ribulokinases using this experimental approach as a starting point ( 78 ).…”
Section: Experimental and Computational Strategies To Identify New Mementioning
confidence: 99%